2013
DOI: 10.1155/2013/182472
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Autoantibodies in Pregnancy: Their Role, Regulation and Clinical Relevance

Abstract: Autoantibodies to thyroglobulin and thyroid peroxidase are common in the euthyroid population and are considered secondary responses and indicative of thyroid inflammation. By contrast, autoantibodies to the TSH receptor are unique to patients with Graves' disease and to some patients with Hashimoto's thyroiditis. Both types of thyroid antibodies are useful clinical markers of autoimmune thyroid disease and are profoundly influenced by the immune suppression of pregnancy and the resulting loss of such suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 161 publications
(180 reference statements)
2
82
1
7
Order By: Relevance
“…9 The interplay between TSH-receptor stimulating and blocking antibodies might explain the switch from hypothyroidism to hyperthyroidism and vice versa. 86,87 Suggestion:…”
Section: Suggestionmentioning
confidence: 99%
“…9 The interplay between TSH-receptor stimulating and blocking antibodies might explain the switch from hypothyroidism to hyperthyroidism and vice versa. 86,87 Suggestion:…”
Section: Suggestionmentioning
confidence: 99%
“…Both TPO and Tg are essential in the synthesis and secretion of thyroid hormones, including thyroxine (T4) and triiodothyronine (T3) [1][2][3]. Autoantibodies to TPO (TPOAb) and Tg (TgAb) are considered secondary responses and indicative of thyroid inflammation, and can be detected in 10-20 % of women at childbearing age [4,5]. Production of the above autoantibodies implicates the activation of an autoimmune process in the thyroid gland, but the majority of women with positive thyroid autoantibodies are euthyroid, that is, they have normal thyroid function [6].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a smaller prospective study, pregnant women showed a similar decrease of thyroid antibodies during pregnancy with a rebound of anti‐TPO but not of anti‐Tg antibodies at postpartum . The decrease of thyroid antibodies is attributed to the development of maternal immunotolerance during pregnancy . Autoimmune thyroiditis is a Th1‐ and Th17‐driven disease.…”
Section: Introductionmentioning
confidence: 79%